Yes, there is a medial nucleus of the trapezoid body in humans - Kulesza, Randy J.; Grothe, Benedikt (Frontiers in Neuroanatomy, 2015)
The medial nucleus of the trapezoid body (MNTB) is a collection of brainstem neurons that function within the ascending auditory pathway. MNTB neurons are associated with a number of anatomical and physiological specializations which make these cells especially well-equipped to provide extremely fast and precise glycinergic inhibition to its target neurons in the superior olivary complex and ventral nucleus of the lateral lemniscus. The inhibitory influence of MNTB neurons plays essentials roles in the localization of sound sources and encoding temporal features of complex sounds. The morphology, afferent and efferent connections and physiological response properties of MNTB neurons have been well characterized in a number of laboratory rodents and some carnivores. Furthermore, the MNTB has been positively identified in all mammals examined, ranging from opossum and mice to chimpanzees. From the early 1970’s through 2009, a number of studies denied the existence of the MNTB in humans and consequentially, the existence of this nucleus in the human brain has been debated for nearly 50 years. The absence of the MNTB from the human brain would negate current principles of sound localization and would require a number of novel adaptations, entirely unique to humans. However, a number of recent studies of human post-mortem tissue have provided evidence supporting the existence of the MNTB in humans. It therefore seems timely to review the structure and function of the MNTB, critically review the literature which led to the denial of the human MNTB and then review recent investigations supporting the existence of the MNTB in the human brain.